Cerebral Palsy Challenges for the Future - Svraka, Emira (IntechOpen, 2014)
Writing a comprehensive scientific book about the cerebral palsy is a great challenge. Many different interventions are available for persons with CP. Increasingly, it is recognized that intervention needs to be evidence-based and family-centered. Related therapies can offer improvement in some cases but do not offer a cure. Lifelong re/habilitation (habilitation and rehabilitation) in person with cerebral palsy is the first part of this book which has four chapters about management in children and adults with cerebral palsy through the life span, providing support and services. Three chapters of the second part are exploring the new therapy options which could improve the family quality of life. Third part has two chapters about complementary therapies with new possibilities for the future.